The Committed Objectivity of Science and the Importance of Scientific Knowledge in Ethical and Political Education - Duarte, Newton [UNESP]; Massi, Luciana [UNESP]; Teixeira, Lucas André [UNESP] (Springer Nature, 2021)
Despite advances in discussions about the nature of science, there is still a paucity of discussion on the ontological dimension of science in science education research that makes it difficult to defend its content and teaching. In this article, the reasons for trusting science and science education are analyzed through three arguments. The first is that both the belligerent obscurantism and fake news of the ultra-right and the postmodern relativism of sections of the leftwing are connected to objective movements from the capitalist socioeconomic reality. The reestablishment of trust in science and its teaching requires an effort to understand the contemporary social contradictions, problems, and challenges. The second argument is that scientific knowledge does not need to abdicate objectivity in order to ground ethical and political positions. The third argument is that the socialization of scientific knowledge through school education is a necessary, albeit insufficient, condition for the ethical–political education of younger generations. The article concludes by stating that it is necessary to overcome the choice between an education that is supposedly neutral in political and ideological terms and an education that rejects the socialization of scientific knowledge in the name of respecting the multiplicity of culturally rooted voices from within the different oppressed groups present in today’s society.